Recent Advances in Anticancer Chemotherapeutics based upon Azepine Scaffold - Singh, Sarbjit; Goo, Jail; Gajulapati, Veeraswamy; Chang, Tong-Shin; Lee, Kyeong; Choi, Yongseok (Anti-Cancer Agents in Medicinal Chemistry, 2016)
In the recent few years, the emergence of heterocyclic ring-containing anti-cancer agents has gained a great deal of attention among medicinal chemists. Among these, azepine-based compounds are particularly becoming attractive recently. In this Focus Review, we highlight the recent advancements in the development of azepine-based anti-cancer compounds since the year 2000.
Keywords: Anticancer agents